Collaborative interactions among preschool children in a computer environment - Ahmad, Mohd Sharani; Adam Assim, Mohamad Ibrani Shahrimin (Universiti Putra Malaysia Press, 2003)
This paper reports on a study which investigated the collaborative interaction patterns exhibited by five-year-old pre-primary children in an educational computer environment. A case study method was used in one pre-primary centre in a metropolitan city, to examine the patterns of collaborative interaction among young children whilst engaged, in dyads, with the computer within a naturalistic classroom environment. A total of 243 interactions were identified and classified into 16 interaction patterns. Factors facilitating and inhibiting collaborative interaction were identified as: developmental appropriateness of the software; preexisting computer competency and attitude towards computer; mutual friendship between collaborators; children's social goals; appropriate structure of enjoyable learning environment; mutual understanding of the turn-taking system; and non-isolated physical settings. In effect, this study shows that early childhood educators will be in a better position to integrate the computer into their classroom and to promote positive prosocial interaction among children whilst engaged at the computer, if it were to be afforded the same status as other traditional early childhood learning materials and activities.